Romania: university and politics in the 1980s. Case study: the University of Bucharest, the 1980s - Rotaru, Mirela (Journal of Education Culture and Society, 2020)
The presentation I am submitting to your attention focuses on how the University of Bucharest operated during the 1980’s, a very difficult period for Romania. As to be expected, the University of Bucharest, like the entire Romanian education system, took the full blow of communist experimental policies, reflecting quite accurately the general developments of the political system in Romania in the 1980s. The structure of Bucharest University, the curriculum, acceptance of the students via admission exams as well as the process of assignment of graduates from University of Bucharest to production units in the 1980’s, are aspects of university life which were all affected by profound changes during the period subject to the research, leading to a genuine phenomenon in the Romanian society. The way these changes were reflected in the cultural mindset and the traumas generated by them are all points of interest addressed in my presentation.